2021
DOI: 10.1186/s12887-021-03020-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parental knowledge, attitudes and practices regarding antibiotic use in acute upper respiratory tract infections in children under 18 years of age: a cross-sectional study in Turkey

Abstract: Background Upper respiratory tract infections (URTIs) are common in children. Antibiotics still continue to be prescribed although most URTIs are of viral origin. This is inappropriate use and this unnecessary administration contributes or may cause antibiotic resistance. The problem of unnecessary antibiotic use among children is a concern for antibiotic resistance in low- and middle-income developing countries. This study aims to evaluate the knowledge and attitudes of parents of children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…The literature reveals a significant correlation between parents' education and the rational use of antibiotics. It has been shown that parents with lesser education, those living in the rural areas and in less-developed countries have low knowledge and attitude scores (19)(20)(21)(22). In our study, we observed that although a large part of the parents had a high school or university education, a correlation was still found between education and the rational use of antibiotics; we saw that as education levels increased, knowledge and attitude scores regarding the rational use of antibiotics increased.…”
Section: Discussionsupporting
confidence: 48%
“…The literature reveals a significant correlation between parents' education and the rational use of antibiotics. It has been shown that parents with lesser education, those living in the rural areas and in less-developed countries have low knowledge and attitude scores (19)(20)(21)(22). In our study, we observed that although a large part of the parents had a high school or university education, a correlation was still found between education and the rational use of antibiotics; we saw that as education levels increased, knowledge and attitude scores regarding the rational use of antibiotics increased.…”
Section: Discussionsupporting
confidence: 48%
“…Although we did not uncover predictors of antibiotic usage in our study, presumably due to the relatively small sample size, there is much evidence in the literature reporting certain factors influencing the rate of antibiotic use. For instance, a previous study that used a relatively larger sample size (i.e., 2,157) identified poor parental knowledge of antibiotics as a predictor of antibiotic use, whereas our sample is smaller, which precludes the observance of statistically significant factors affecting antibiotic use [20]. Irrational antibiotic use may also be influenced by parents' poor socioeconomic status, low education, and certain behavioral factors, such as self-medication use practice [9,10,17,20].…”
Section: Discussionmentioning
confidence: 79%
“…There is a misunderstanding by physicians during patient consultations, without clearly referring to a viral or bacterial disease. Therefore, some tend to often give antibiotics to treat all kinds of germs infections without recognizing the underlying cause, and antibiotics have been treated as a "wonder drug" by some to treat all kinds of symptoms (Shehadeh et al, 2012;Albayrak et al, 2021;Rahman et al, 2016;Peng et al, 2018).…”
Section: Resultsmentioning
confidence: 99%